Targeted ablation of epicardial ganglionated plexi during cardiac surgery with pulsed field electroporation (NEURAL AF) - Musikantow, Daniel R; Reddy, Vivek Y; Skalsky, Ivo; Shaburishvili, Tamaz; van Zyl, Martin; O'Brien, Barry; Coffey, Ken; Reilly, John; Neuzil, Petr; Asirvatham, Samuel; de Groot, Joris R (Journal of interventional cardiac electrophysiology, 2025)
BACKGROUND: Modulation of the cardiac autonomic nervous system (ANS) is a promising adjuvant therapy in the treatment of atrial fibrillation (AF). In pre-clinical models, pulsed field (PF) energy has the advantage of selectively ablating the epicardial ganglionated plexi (GP) that govern the ANS. This study aims to demonstrate the feasibility and safety of epicardial ablation of the GPs with PF during cardiac surgery with a primary efficacy outcome of prolongation of the atrial effective refractory period (AERP). METHODS: In a single-arm, prospective analysis, patients with or without a history of AF underwent epicardial GP ablation with PF during coronary artery bypass grafting (CABG). AERP was determined immediately pre- and post- GP ablation to assess cardiac ANS function. Holter monitors were performed to determine rhythm status and heart rate variability (HRV) at baseline and at 1-month post-procedure. RESULTS: Of 24 patients, 23 (96%) received the full ablation protocol. No device-related adverse effects were noted. GP ablation resulted in a 20.7 ± 19.9% extension in AERP (P < 0.001). Post-operative AF was observed in 7 (29%) patients. Holter monitoring demonstrated an increase in mean heart rate (74.0 ± 8.7 vs. 80.6 ± 12.3, P = 0.01). There were no significant changes in HRV. There were no study-related complications. CONCLUSIONS: This study demonstrates the safety and feasibility of epicardial ablation of the GP using PF to modulate the ANS during cardiac surgery. Large, randomized analyses are necessary to determine whether epicardial PF ablation can offer a meaningful impact on the cardiac ANS and reduce AF. TRIAL REGISTRATION: Clinical trial registration: NCT04775264.
Keywords: výsledek terapie; koronární bypass; Cardiac autonomic nervous system; Male; perikard; Post-operative atrial fibrillation; Ganglia, Autonomic; Coronary Artery Bypass; Aged; Prospective Studies; mužské pohlaví; senioři; Catheter Ablation; Atrial Fibrillation; Pericardium; Treatment Outcome; Electroporation; lidé; ženské pohlaví; Feasibility Studies; Pulsed field ablation; Humans; ganglia autonomní; Electrocardiography, Ambulatory; elektroporace; Atrial fibrillation; elektrokardiografie ambulantní; katetrizační ablace; Female; studie proveditelnosti; lidé středního věku; fibrilace síní; Middle Aged; prospektivní studie